Development of Android Application in Enhancing Learning in Japanese Kanji. - Haristiani, Nuria; Aryadi, Suhendar (Pertanika Journal of Social Sciences & Humanities)
This study is aimed at developing a suitable media for improving learning of Japanese kanji using an android application. The authors also examined the effectiveness of current application to learning basic Japanese. Utilising Information and Communication Technology (ICT) is not common. The media proposed in this study is also suitable for students who are learning independently. Further, this media is based on spacing effect theory, which has a huge impact in helping and improving long-term memory. Since the media uses an Android application, there is no age, grade, and level constraints. Further, the student is able to use the application wherever they are and whenever they have the time to learn. The media is also attractive, easy-to-use, and helps students to easily memorise Kanji.